European Agency Statistics on Inclusive Education: 2014 Dataset Cross-Country Report - European Agency For Special Needs And Inclusive Education (Zenodo, 2017)
The 2014 Dataset Cross-Country Report is based on the first European Agency Statistics on Inclusive Education (EASIE) dataset collected in late 2014/early 2015, focusing upon the school year 2012–2013. The report presents the agreed data from participating countries in a cross-country format that has the potential to directly inform the work of national and European level policy- and decision-makers working in the field of education. It presents data relating to 17 indicators that were identified and agreed upon with the national data experts. The indicators are based on three areas of country data: Population and enrolment data taken from Table 1 Age sample data (9 and 15-year-olds) taken from Table 2 Data on pupils with an official decision of special educational needs (SEN) taken from Table 3, including identification rates, distributions of educational placements taken from Table 3, along with gender and International Standard Classification of Education (ISCED) breakdowns of this data taken from Tables 4, 5 and 6. The report is structured around these three areas, with descriptive texts and figures presenting all available country data for each indicator. It covers data from the following participating countries: Belgium (Flemish community), Belgium (French community), Croatia, Cyprus, Czech Republic, Denmark, Estonia, Finland, France, Germany, Hungary, Iceland, Ireland, Latvia, Lithuania, Luxembourg, Malta, Netherlands, Norway, Poland, Portugal, Slovakia, Slovenia, Spain, Sweden, Switzerland, UK (England), UK (Northern Ireland), UK (Scotland) and UK (Wales). Download the report below as a Word document in English. : This publication has been funded with support from the European Commission. This publication reflects the views only of the author, and the Commission cannot be held responsible for any use which may be made of the information contained therein. : {"references": ["European Agency for Special Needs and Inclusive Education, 2017. European Agency Statistics on Inclusive Education: 2014 Dataset Cross-Country Report. (J.\u00a0Ramberg, A.\u00a0L\u00e9n\u00e1rt, and A.\u00a0Watkins, eds.). Odense, Denmark"]}